Benefits of the Principles of Perry Neighborhood Unit through Supply Chain Strategy in Nong Chik Heights, Johor Bahru, Malaysia - Jumadil Saputra; Rahaya Md. Jamin; Siti Aisyah Saat; Rozita Muhamad Nawi; Mohd Najib Ramli (International Journal of Supply Chain Management, 2019)
This study attempts to investigate the combination of new towns concept goal of honeycomb concepts integrated through the application of the supply chain strategy in Perry Neighborhood Unit Principles founded on "the life of a family community" to achieve the balance of human life. The combination of these goals provides the concept of new housing by applying the social element in physical influences so that the elements of village goodness that once existed in the past can be restored in the goodness of today's urban community. The aims of this study is to identify the Principles of Perry Neighborhood Unit through supply chain strategy that is applied in the implementation of the concept of honeycomb and the benefits obtained from the application. This study using participant observation, in-depth interviews and questionnaires. The 275 samples were selected as respondents (questionnaire through cluster sampling technique) while 3 as a subject of study (in-depth interviews with study techniques chain). The success of the concept of honeycomb in Nong Chik Heights has influenced People's Dream House Policy under the National Affordable Housing Policy (2018-2025). This study found that the concept of honeycomb apply the objective of affordable houses, namely, ensuring quality and cohesive neighborhoods by providing and maintaining facilities and quality services in the neighborhood to support the life of the community. It is in line with the slogan of â€œhousing for all and quality homes of hope of the peopleâ€.